The Role of Halal Industry in Driving Bilateral Economic Diplomacy Between Indonesia and Turkiye - Hidayati, Ratnaningsih (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This article investigates how the halal industry can promote economic relations and trade diplomacy between Indonesia and Turkiye. Both countries recognize the benefits of the halal industry in expanding exports, attracting foreign investments, and showcasing their cultural and religious values. The purpose of this paper is to investigate how the halal industry can facilitate economic diplomacy between Indonesia and Turkiye. Study conducted through a qualitative approach by doing literature review on trade statistics, government policies, and business strategies to identify the opportunities and challenges for both countries in utilizing the halal industry. Additionally, it explores potential areas for cooperation in halal certification, halal tourism, and halal food processing. By prioritizing the halal industry through the halal powerhouse, Indonesia and Turkiye can strengthen their bilateral economic cooperation, diversify their exports, and enhance their soft power in the global arena.